Antimicrobial Treatment of Human Plague: A Systematic Review of the Literature on Individual Cases, 1937–2019. (21st May 2020) - Nelson, Christina A; Fleck-Derderian, Shannon; Cooley, Katharine M; Meaney-Delman, Dana; Becksted, Heidi A; Russell, Zachary; Renaud, Bertrand; Bertherat, Eric; Mead, Paul S
Abstract: Background: Yersinia pestis remains endemic in Africa, Asia, and the Americas and is a known bioterrorism agent. Treatment with aminoglycosides such as streptomycin or gentamicin is effective when initiated early in illness but can have serious side effects. Alternatives such as fluoroquinolones, tetracyclines, and sulfonamides are potentially safer but lack robust human data on efficacy. Methods: We searched PubMed Central, Medline, Embase, and other databases for articles in any language with terms related to plague and antimicrobials. Articles that contained case-level information on antimicrobial treatment and patient outcome were included. We abstracted information related to patient demographics, clinical features, treatment, and fatality. Results: Among 5837 articles screened, we found 762 published cases of treated plague reported from 1937 to 2019. Fifty-nine percent were male; median age was 22 years (range, 8 days–80 years). The case fatality rate was 20% overall. Most patients had primary bubonic (63%), pneumonic (21%), or septicemic (5%) plague, with associated case fatality rates of 17%, 27%, and 38%, respectively. Among those treated with an aminoglycoside (n = 407 [53%]), the case fatality rate was 13%. Among those treated with a sulfonamide (n = 322 [42%]), tetracycline (n = 171 [22%]), or fluoroquinolone (n = 61 [8%]), fatality was 23%, 10%, and 12%, respectively. Case fatality rate did not substantially differ between patients treated with 1 vs 2 classes of antimicrobials considered to be effective for plague. Conclusions: In addition to aminoglycosides, other classes of antimicrobials including tetracyclines, fluoroquinolones, and sulfonamides are effective for plague treatment, although publication bias and low numbers in certain treatment groups may limit interpretation. Abstract : Among 744 published cases of plague, fatality rates were similar for patients treated with aminoglycosides, tetracyclines, and fluoroquinolones. Treatment with sulfonamides was not commonly reported in recent decades. Dual antimicrobial therapy did not appear to improve outcomes compared to monotherapy.